A global review of the downstream effects of small impoundments on stream habitat conditions and macroinvertebrates - Mbaka, John Gichimu; Mwaniki, Mercy Wanjiru (NRC Research Press, 2015)
The downstream ecological effects of large impoundments have previously been reviewed; however, little is known about the downstream ecological effects of small man-made impoundments. In this review, we examine 94 papers focusing on theeffectsofsmallimpoundmentsonstreamhabitatconditionsandmacroinvertebrates.Moststudies(89.3%)address the effects of small impoundments on physical and chemical habitat conditions, while fewer studies (48.9%) address the effects on macroinvertebrates. In general, most studies report no signiﬁcant downstream effects of small impoundments on physico-chemical variables, whereas macroinvertebrates richness and abundance increased or decreased. Mean effect sizes (as Cohen’s d) for physico-chemical variables range from −0.82 to 0.68 (small weir: −0.21 to 0.35; run-of-river dam: −0.82 to 0.64; low head dam: −0.49 to 0.68),and from−0.03to0.63formacroinvertebratesabundanceandrichness.Ourassessmentofthepublishedliterature demonstratestheadvantageofcombiningqualitativeandquantitativeanalyses,and that,while small impoundments may have minimal signiﬁcant effects on most physico-chemical variables,macroinvertebrates’richness and density may be affected.This review is relevant for management and scientiﬁc communities to identify potential alterations of stream habitats and biota by small impoundments
Keywords: Impoundments; Stream invertebrates; River; Environment; Ecological effects; Physico-chemical variables